Kontekstualisasi Fikih Melalui Prinsip Kemaslahatan - Ansori Ansori (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2008)
The existence of Islamic law (fiqh) wich is able to improve the society condition and to solve many problems is such a fact. Contextualize needs to be done continuously and one of the guidance is goodness principal.